Peningkatan Hasil Belajar Matematika pada Materi Satuan Waktu Melalui Model Problem Based Learning Berbantuan Media Papan Waktu pada Siswa Kelas II SDN 13 Mataram - Apriliani, Ni Putu Wangi; Swari I, Ni Made Puja; Rohyani, Helmi; Arjudin, Arjudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This article aimed to explain efforts to improve student learning outcomes in unit time material through the use of the Problem-Based Learning (PBL) model assisted by time board media in class II students at SDN 13 Mataram. Classroom action research was conducted to see the impact of applying this learning model on understanding and students' skills in understanding the concept of a unit of time. The research method used is an action cycle that involved planning, implementing, observing, and reflecting. In the planning stage, a lesson plan was designed taking into account the characteristics of the students and the desired learning objectives. Then, learning actions were carried out using the PBL model assisted by time board media. Observations were made to monitor student progress during learning. After that, reflected on the learning process and the results that have been achieved. The study results showed that applying the PBL model assisted by time board media can improve student learning outcomes in the unit time material. Students’ ability increased in understanding the concept of units of time, calculating time, and solving problems related to units of time. The application of this model provided an opportunity for students to be actively involved in the learning process and visualized the concept of a unit of time concretely. These findings indicate that the PBL model assisted by time board media is an effective alternative in teaching unit time material to second-grade students. The recommendation of this study is to encourage mathematics teachers to consider using this model as a strategy.